Boars exposed to contrasting housing environments and the welfare consequences for their offspring - Sabei, Leandro (2024)
Boars in commercial environments or experience poor welfare due to restricted movement, social isolation, and exposure to minimal environmental stimuli. Stressful factors in males cause changes in semen quality and can influence how genetic information is transferred to the offspring. This study hypothesizes that the boars environment alters the offspring′s epigenome and modulates their subsequent development. The project aims to evaluate the possible intergenerational effects of male pigs exposed to different housing conditions on the development of their offspring. Three environmental conditions were used to individually house 18 boars: crates (C), pens (P), and enriched pens (E) (n=6/treatment). Semen pooled from boars representing all three treatment groups was used to inseminate outdoor-housed gilts. Behavioral and salivary cortisol data were collected during the gestation period. After farrowing, piglets were identified with ear tags. Piglet mortality rate and weight were recorded, and behavior and vocalizations were evaluated during three emotional tests (open field, novel object, and elevated plus maze). At 29 days of age, piglets were weaned, and skin lesions and nociceptive threshold were assessed. Saliva samples were collected to measure cortisol before and after the open field/novel object test and weaning. Hair samples from boars and piglets were used for a paternity test. At 70 days after birth, only male piglets were slaughtered, and their brains were extracted and frozen. The piglet′s pre-frontal cortex tissue was macerated, and the glucocorticoids were extracted and measured, using EIA. Appropriate statistical methods were used for each type of data (p<0.05). The results revealed that females with higher social status have heavier piglets. Additionally, results showed that more piglets fathered by boars housed in E compared to P were born alive and survived to weaning. The offspring from boars in P showed higher mean nociceptive values compared to boars in C. Furthermore, behavioral testing yielded a significant difference as C sired piglets exhibited less activity/fear compared to E. However, C sired piglets showed higher amounts of anxiety and inactivity away from an object/exploration compared to piglets from P. The ratio of salivary cortisol in piglets born to E boars was higher than in piglets born to either P or C boars. In comparison to piglets from P and E males, piglets born from C males emitted more longer duration, higher low frequency vocalizations, indicating a more aversive experience during the tests. There was no difference in glucocorticoids in brain tissue. The environment where boars are housed contributes to phenotypic changes in their descendants. Therefore, enhancing parental welfare can improve offspring′s resilience and welfare too.